2012
DOI: 10.1111/j.1462-5822.2012.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa biofilm-associated homoserine lactone C12 rapidly activates apoptosis in airway epithelia

Abstract: Pseudomonas aeruginosa (PA) forms biofilms in lungs of cystic fibrosis CF) patients, a process regulated by quorum sensing molecules including N-(3-oxododecanoyl)-L-homoserine lactone, C12. C12 (10–100 μM) rapidly triggered events commonly associated with the intrinsic apoptotic pathway in JME (CFΔF508CFTR, nasal surface) epithelial cells: depolarization of mitochondrial (mito) membrane potential (Δψmito) and release of cytochrome C (cytoC) from mitos into cytosol and activation of caspases 3/7, 8 and 9. C12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 60 publications
12
95
0
Order By: Relevance
“…Calu-3 cells routinely had transepithelial resistance (RT) Ͼ400 ⍀·cm 2 and exhibited polarized responses consistent with previous studies (5,33). JME cells, a continuous SV40 large-T antigen-transformed human nasal epithelial cell line homozygous for ⌬F508 CFTR, were used for many imaging experiments, because they exhibit a higher transfection efficiency than Calu-3 cells and have excellent imaging properties (27)(28)(29). JME cells were cultured in DMEM-Ham's F-12 medium supplemented with 10% FBS, 2 mM L-glutamine, 1% penicillinstreptomycin, 10 ng/ml EGF, 1 M hydrocortisone, 5 g/ml insulin, 5 g/ml transferrin, 30 nM triiodothyronine, 180 M adenine, and 5.5 M epinephrine.…”
Section: Methodssupporting
confidence: 73%
See 4 more Smart Citations
“…Calu-3 cells routinely had transepithelial resistance (RT) Ͼ400 ⍀·cm 2 and exhibited polarized responses consistent with previous studies (5,33). JME cells, a continuous SV40 large-T antigen-transformed human nasal epithelial cell line homozygous for ⌬F508 CFTR, were used for many imaging experiments, because they exhibit a higher transfection efficiency than Calu-3 cells and have excellent imaging properties (27)(28)(29). JME cells were cultured in DMEM-Ham's F-12 medium supplemented with 10% FBS, 2 mM L-glutamine, 1% penicillinstreptomycin, 10 ng/ml EGF, 1 M hydrocortisone, 5 g/ml insulin, 5 g/ml transferrin, 30 nM triiodothyronine, 180 M adenine, and 5.5 M epinephrine.…”
Section: Methodssupporting
confidence: 73%
“…Recent work on fibroblasts has shown that C12-triggered apoptosis, including release of cytochrome c from mitochondria, occurs independent of the proapoptotic mediators Bak and Bax (28). Importantly, P. aeruginosa biofilms elicited lasI-dependent (lasI is the enzyme responsible for synthesis in P. aeruginosa) increases in cytosolic Ca 2ϩ concentration (Ca cyto ) and depolarization of ⌬ mito , indicating that P. aeruginosa biofilms produce sufficient C12 to induce the observed proapoptotic responses (27). It might be expected that biofilm formation and C12-induced host cell apoptosis might be beneficial to the bacteria, in that barrier function may be compromised to permit bacterial access to the body.…”
mentioning
confidence: 99%
See 3 more Smart Citations